Question #4be45

2 Answers
Jan 12, 2018

Read below.

Explanation:

Remember: In an expression, a variable can have any value. You can only solve it when you give it a value.

So the problem is asking us what are the answers if we were to give the x the values of 1,2, and 3. We simply replace x with the numbers.

3x+2 is now
3(1)+2 for x=1
3(1)+2=1

3x+2 is now
3(2)+2 for x=2
3(2)+2=4

3x+2 is now
3(3)+2 for x=2
3(3)+2=7

Jan 12, 2018

3(1)+2=(1)
3(2)+2=(4)
3(3)+2=(7)

Explanation:

Substitute the x values for the expression